(untitled) (CIPEEX, 2026)
This study aims to analyze whether students and teachers in 5th-grade elementary school classes enrolled in municipal public schools in Goianésia, Goiás, Brazil, located in different regions and with varying socioeconomic profiles, have distinct perceptions about environmental education and sustainability, and whether these perceptions are related to their performance on the IDEB (Basic Education Development Index). Implemented in 2007, the IDEB assesses the quality of basic education teaching and is applied to the 5th, 9th, and 3rd grades because they represent decisive cycles of schooling. The research will involve students from one 5th-grade class (average age of 10) from each of the 13 municipal elementary schools in Goianésia, Goiás, Brazil, which underwent IDEB assessments in 2023. Data collection will be carried out through questionnaires administered to 29 students and one teacher from each school unit, seeking to identify perceptions about environmental education. These data will be cross-referenced with academic performance and socioeconomic indicators to understand the relationship between environmental awareness and educational quality. A mixed methodological approach will be adopted: qualitative, with theoretical analysis based on specialized literature; and quantitative, through a questionnaire with objective questions, the answers to which will be organized and quantified using simple statistical methods. The research is expected to demonstrate how environmental awareness can act as a factor in strengthening educational quality, highlighting the importance of critical and sustainable pedagogical practices. Keywords: IDEB, spatial analysis, spatial indices, environment